(untitled) (Journal of Economic Research & Business Administration, 2023)
The modern practice of the formation and development of regional tourism makes it necessary to revise the traditional methods and tools for the destination development, and as a result, the theoretical understanding of the ongoing processes and the development of ways to increase the attractiveness of the regional tourism product. Government is developing certain tourist regions, first focusing on the most promising areas, where there is a high potential for attracting a tourist flow. One of them is Mangistau region, which is included in the top 10 tourist destinations of the country. The purpose of this study is to conduct a factorial and comparative analysis of the development of the tourism industry in Mangistau. The following scientific methods were used during the study: content analysis, statistical data collection method and PEST analysis. As a result of the analysis, problems were identified in the development of the tourism industry in the Mangistau region, key factors and points of their influence on certain sectors of tourist recreation were identified, and recommendations were made to address existing problems and increase the attractiveness of the regional tourism product, which are presented in the final part of this article, which is the value of the study. Based on the results of the factor analysis, the authors developed a visual diagram, where the cycle of each factor shows the point of influence on a particular sector. The measures proposed in the article, aimed primarily at unifying their own attractiveness for the tourist flow, both in the domestic and international markets, will form a scientific basis for making decisions by the local executive authorities for the future prospects of the tourism industry in the Mangistau region. Key words: tourism, analysis, regional tourism product, Mangistau region, tourism industry.